New horizons in live and dehydrated black soldier fly larvae usage: Behavioral and welfare implications in “Bianca di Saluzzo” cockerels - Valentina Bongiorno; Edoardo Fiorilla; Marta Gariglio; Valeria Zambotto; Eleonora Erika Cappone; Stefania Bergagna; Isabella Manenti; Elisabetta Macchi; Francesco Gai; Achille Schiavone (PLoS ONE, 2025)
The literature on poultry welfare and behavior reports numerous promising effects derived from the administration of live or dehydrated black soldier fly larvae (BSFL) as environmental enrichment; however, their use in slow-growing male chickens has never been evaluated. To fill this gap, we divided a total of 144 Bianca di Saluzzo male chicks aged 39 days old into three experimental groups (six replicates, eight birds/replicate): control (C, no enrichment provided), dehydrated larvae (DL, 4.12% as fed), and live larvae (LL, 15.38% as fed), and reared until 147 days of age. Explorative and aggressive behavior patterns were analyzed, in concomitance with a tonic immobility test and the avoidance distance test, heterophile to lymphocyte -H/L- ratio), and excreta corticosterone metabolites (ECM) matrices. Overall, LL and DL supplementation were both effective at mitigating aggressive interactions among chickens (P < 0.05), while the frequency of indoor explorative behavior was lower in the LL group compared with C and DL (P < 0.01). By contrast, we found no differences in fear reduction during the avoidance distance test in the LL or DL groups compared with C (P < 0.05). We found a trend for the H/L ratio to be C < LL<DL (P = 0.051), and ECM concentrations were significantly lower in DL and LL groups compared with C (P < 0.001). In conclusion, the use of DL and LL as environmental enrichment have the potential to produce beneficial outcomes in slow-growing male chickens.